In state of precarity narratives of pinay house helpers and the filipino diaspora in Dubai - Fortich, Christian L. (2022)
This study aims to understand the lives of Filipina house helpers in Dubai, United Arab Emirates by looking at the ways and means of arrival to the country of deployment, past employment experiences, current working conditions, and prospects upon retirement. This study also examines the manifestations of some dimensions of diaspora and how the Filipino community impacts the living conditions of the house helpers. The study uses the snowball sampling method and has a total number of 10 interlocutors. The respondents are subjected to semi?structured and unstructured interviews to arrive at the answers to the research questions. In analyzing the answers, this study utilizes the theoretical proportions of the Precarity Chains- precarity of migration, precarity of labor, and precarity of the future ? as forwarded by Rachel Parrenas and Racel Silvey (2019). In studying diasporic dimensions, this thesis engages with the three of five theoretical propositions of Filomeno Aguilar?s Diaspora: the ongoing relationship with the homeland, idealization of return, and collective consciousness. Data shows that people who arrived in Dubai using tourist visas are more prone to precarious situations than compared to Filipino domestic workers who went to the UAE through recruitment agencies as posited by the precarity of migration. As for the precarity of labor, while the findings reveal that no respondents suffer a lack of social benefits or legal protection, the kafala system is widely practiced in the UAE. As such, there is a need for a functioning and proactive Philippine iplomatic representation that can serve as a safety net migrant workers in times of trouble or abuse. In terms of precarity of the future, the study finds that the lack of assets on the part of the house helper unearths societal problems like inaccessibility of social and medical services in the homeland. As for diasporic dimensions, the ongoing relationship of domestic helpers with the homeland is manifested through monthly remittances. The idealization of return depends on one?s savings and investments back in their homeland. Collective consciousness is seen in how events in the Filipino community provide house helpers the avenue to bond and have a comparative view of their working conditions. Moving forward, this study proposes to expand the discussion on the precarity of migration and include the Filipino house helpers who leave with tourist visas and the probable uncertainties attached to it.